If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + (6x + -1) = 90 Reorder the terms: 7x + (-1 + 6x) = 90 Remove parenthesis around (-1 + 6x) 7x + -1 + 6x = 90 Reorder the terms: -1 + 7x + 6x = 90 Combine like terms: 7x + 6x = 13x -1 + 13x = 90 Solving -1 + 13x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 13x = 90 + 1 Combine like terms: -1 + 1 = 0 0 + 13x = 90 + 1 13x = 90 + 1 Combine like terms: 90 + 1 = 91 13x = 91 Divide each side by '13'. x = 7 Simplifying x = 7
| n+4=15 | | d+5=0 | | b+6=7 | | Z/-6=-2 | | -19=t-8 | | 3+n=13 | | 4t=0 | | a+9=5 | | 7d=-14 | | 4=t+4 | | 14=a+8 | | a/3=-7 | | 19=k+7 | | t-1=0 | | x(5-x)+2= | | w-2=-11 | | -6a=-12 | | w+6=-6 | | 5+n=5 | | w+9=15 | | t/7=-6 | | k/4=-2 | | 6=n+2 | | k+7=-3 | | 3=w-2 | | x+4=2x-8(1/4x-1/4) | | -1/39-7=-3 | | -7x^2+6x^2-8x^2= | | m/2=5 | | k/3=-7 | | 4(x-1)-2(3x+5)=-3x-1 | | -14=a-5 |